2010
DOI: 10.1177/1059840510394189
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of the Rural School’s Role in Addressing Childhood Obesity

Abstract: This study employed cross-sectional, descriptive design with convenience sampling to explore rural parent perceptions of child obesity, use of Body Mass Index (BMI) in schools, preferences for receipt of BMI information and, the rural school's role in obesity prevention/treatment. The survey "Parental Perceptions of BMI and Obesity in the School-Age Child" was used. Of the 183 surveys distributed, 65 were returned (35.5%). Fifty-five percentage of parents were in agreement of school-based BMI screening. Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(63 reference statements)
2
12
0
Order By: Relevance
“…Complicating the issue is that states that conduct school‐based BMI screenings often implement additional school policies for reducing obesity, such as (1) increasing physical activity; (2) removing/improving vending machine offerings; (3) limiting access to vending; (4) improving school lunches; (5) providing nutrition programs; extending students' lunchtime; (6) prohibiting sale of “junk” foods at school‐sponsored activities; (7) prohibiting use of physical activity for punishment; (8) hiring certified physical education (PE) teachers; and (9) increasing awareness about childhood obesity and weight‐related health risks . Although 1 study found that parents were less likely to support school changes and weight interventions if their children were overweight or obese, assessment data from Arkansas revealed that overall families became more aware of weight‐related health problems and made physical activity a more significant priority, adolescents increased physical activity, and students reduced vending purchases and consumption of sodas and fast foods…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complicating the issue is that states that conduct school‐based BMI screenings often implement additional school policies for reducing obesity, such as (1) increasing physical activity; (2) removing/improving vending machine offerings; (3) limiting access to vending; (4) improving school lunches; (5) providing nutrition programs; extending students' lunchtime; (6) prohibiting sale of “junk” foods at school‐sponsored activities; (7) prohibiting use of physical activity for punishment; (8) hiring certified physical education (PE) teachers; and (9) increasing awareness about childhood obesity and weight‐related health risks . Although 1 study found that parents were less likely to support school changes and weight interventions if their children were overweight or obese, assessment data from Arkansas revealed that overall families became more aware of weight‐related health problems and made physical activity a more significant priority, adolescents increased physical activity, and students reduced vending purchases and consumption of sodas and fast foods…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…A significant benefit attributed to screening programs is the way data are collected to monitor obesity trends for various demographic subgroups at state and local levels, including rural areas where data are often limited . The standardized assessment of BMI data collected by trained personnel are more valid and reliable than the self‐ or parent‐reported data used for most national estimates .…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MA, schools were required to notify parents in advance to provide the opportunity to opt out of the BMI screening process. Previous research in other states supports the consensus that parents prefer results not be shared with students in schools and that communication be done via mail [7,3335], which may also be more effective in prompting caregivers to read the letter than sending the letter home from school with a child [36]. Failure to send BMI letters home via mail was cited as one reason that MA voted to end its program [8].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a BMI report card is controversial and research to date has not proven its efficacy in changing weight-related behaviors. [11][12][13] However, one study reported that the use of a personalized weight and fitness health report card intervention did significantly increase awareness and help parents of overweight children to correctly identify their child's weight status. 13 To date, there has not been any information published about the use of BMI report cards for preschool children.…”
Section: Discussionmentioning
confidence: 99%